The role of follow-up ultrasound and clinical parameters after abdominal MDCT in patients with multiple trauma. (May 2014) - Geyer, Lucas L; Körner, M; Linsenmaier, U; Wirth, S; Reiser, MF; Meindl, T
Background: Beside its value during the initial trauma work-up (focused assessment with sonography for trauma), ultrasound (US) is recommended for early follow-up examinations of the abdomen in multiple injured patients. However, multidetector CT (MDCT) has proven to reliably diagnose traumatic lesions of abdominal organs, to depict their extent, and to assess their clinical relevance. Purpose: To evaluate the diagnostic impact of follow-up US studies after MDCT of the abdomen and to identify possible clinical parameters indicating the need of a follow-up US. Material and Methods: During a 30-month period, patients with suspected multiple trauma were allocated. Patients with admission to the ICU, an initial abdominal MDCT scan, and an US follow-up examination after 6 and 24 h were included. Two patient cohorts were defined: patients with normal abdominal MDCT (group 1), patients with trauma-related pathologic abdominal MDCT (group 2). In all patients, parameters indicating alteration of vital functions or hemorrhage within the first 24 h were obtained by reviewing the medical charts. Results: Forty-four of 193 patients were included: 24 were categorized in group 1 (mean age, 41.1 years; range, 21–90 years), 20 in group 2 (mean age, 36.6 years; range, 16–71 years). In group 1, US did not provide new information compared to emergency MDCT. In group 2, there were no contradictory 6- and 24-h follow-up US findings. In patients with positive MDCT findings and alterations of clinical parameters, US did not detect progression of a previously diagnosed pathology or any late manifestation of such a lesion. In none of the patients with negative abdominal MDCT and pathological clinical parameters US indicated an abdominal injury. Conclusion: Routine US follow-up does not yield additional information after abdominal trauma. In patients with MDCT-proven organ lesions, follow-up MDCT should be considered if indicated by abnormal clinical and/or laboratory findings.